Геолого-структурные особенности Култуминского гранитоидного массива (юго-восточное Забайкалье) - Салихов Владимир Салихович; Груздев Роман Викторович (Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования Забайкальский государственный университет, 2013)
On the basis of modern interpretation of geophysical data the geological and structural position and structure of the Kultuminsky granitoid massif is characterized. The attribute of Kultuminsky ore field to copper-porphyry system that makes an ore field of the southeastern Zabaikalie one of the potentially perspective production objects of copper, molybdenum, gold and other useful components which are of interest in the light of modern technologies development of enrichment is considered. The role of eruptive breccia in formation of mineralization of Kultuminsky ore and magmatic system is defined. The conclusions are drawn on the need of a more detailed study of the Kultuminsky ore field for the purpose of combined Au-Cu-Mo of porphyritic type of mineralization identification, along with the skarn one
Keywords: КУЛТУМИНСКИЙ МАССИВ; МЕДНО-ПОРФИРОВЫЙ ТИП; ГРАНИТОИДЫ; СКАРНОВЫЙ ТИП; ОРУДЕНЕНИЕ; ГЕОФИЗИЧЕСКИЕ МЕТОДЫ ИССЛЕДОВАНИЯ; KULTUMINSKY MASSIF; COPPER-PORPHYRY TYPE; GRANITOIDS; SKARN TYPE; MINERALIZATION; GEOPHYSICAL METHODS OF RESEARCH; 553.3 (571.55)